Surface-templated hydrogel patterns prompt matrix-dependent migration of breast cancer cells towards chemokine-secreting cells. (February 2015) - Kojima, Taisuke; Moraes, Christopher; Cavnar, Stephen P.; Luker, Gary D.; Takayama, Shuichi
Graphical abstract: Abstract: This paper describes a novel technique for fabricating spatially defined cell-laden collagen hydrogels, using patterned, non-adhesive polyacrylamide-coated polydimethylsiloxane (PDMS) surfaces as a template. Precisely patterned embedded co-cultures of breast cancer cells and chemokine-producing cells generated with this technique revealed matrix-dependent and chemokine isoform-dependent migration of cancer cells. CXCL12 chemokine-secreting cells induce significantly more chemotaxis of cancer cells when the 3-D extracellular matrix (ECM) includes components that bind the secreted CXCL12 chemokines. Experimental observations using cells that secrete CXCL12 isoforms with different matrix affinities together with computational simulations show that stronger ligand–matrix interactions sharpen chemoattractant gradients, leading to increased chemotaxis of the CXCL12 gradient-sensing CXCR4 receptor-expressing (CXCR4+) cells patterned in the hydrogel. These results extend our recent report on CXCL12 isoform-dependent chemotaxis studies from 2-D to 3-D environments and additionally reveal the important role of ECM composition. The developed technology is simple, versatile and robust; and as chemoattractant-matrix interactions are common, the methods described here should be broadly applicable for study of physiological migration of many different cell types in response to a variety of chemoattractants.